Physicochemical Characterization of Simplicia Sambiloto (Andrographis paniculata) Powder with Types and Concentrations of Reagents in the Formation of Zn-Chlorophyll Complexes: Karakterisasi Fisikokimia Bubuk Simplisia Sambiloto (Andrographis Paniculata) dengan Jenis dan Konsentrasi Reagen dalam Pembentukan Kompleks Zn-Klorofil - Aziz, M Rifqi; Suryani, Chatarina Lilis; Fitri, Ichlasia Ainul (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2024)
During the process of making sambiloto simplicial which involves heat, it can cause degradation of chlorophyll. Increasing the stability of chlorophyll can be done by forming Zn-chlorophyll complexes with metals which are be able to form complexes where more stable than Mg such as by using Zn. The aim of this research is to determine how the physical and chemical characteristics of the bitter simplicia powder produced are influenced by the type of reagent and the concentration of the reagent when heated in an oven. Simplicia bitter powder is made through a sorting, grinding and sieving process. Next, the zinc chloride and zinc acetate reagents were mixed with concentrations of 0, 200, 300, 400, and 500 ppm, and then dried. The results showed a real effect (p value <0.05) of the interaction between the types of ZnCl2 and Zn acetate reagents and the reagent concentration on color intensity, color stability, water content, ash content and chlorophyll content. The higher the concentration of ZnCl2 and Zn acetate, the higher the water content, ash content, chlorophyll content, L*, and -a*, while b* and ∆E decrease. At a concentration of 500 ppm ZnCl2 showed an increase in water, ash, chlorophyll, ∆E, L*, and a* content while b* decreased. Meanwhile, Zn acetate 500 ppm moisture content, ash content, chlorophyll content, L*, and ∆E decreased, while a* and b* increased. Sambiloto simplicia powder which has the highest chlorophyll content is Zn acetate 400 ppm, with characteristics of water content 6.81% ww, ash content 15.74% ww, total chlorophyll 397.97 mg/100 g ww, green color intensity (-a) -2.93, and ∆E 5.48.